Exploiting antidiabetic activity of silver nanoparticles synthesized using Punica granatum leaves and anticancer potential against human liver cancer cells (HepG2). (2nd January 2018) - Saratale, Rijuta G.; Shin, Han Seung; Kumar, Gopalakrishnan; Benelli, Giovanni; Kim, Dong-Su; Saratale, Ganesh D.
Abstract: This study first time reports the novel synthesis of silver nanoparticles (AgNPs) using a Punica granatum leaf extract (PGE). The synthesized AgNPs were characterized by various analytical techniques including UV–Vis, Fourier transform infrared (FTIR), X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy and energy-dispersive spectra (FESEM-EDS) and high-resolution transmission electron microscopy (HRTEM). FTIR analysis revealed that the involvement of biological macromolecules of P. granatum leaf extract were distributed and involved in the synthesis and stabilization of AgNPs. A surface-sensitive technique of XPS was used to analyse the composition and oxidation state of synthesized AgNPs. The analytical results confirmed that the AgNPs were crystalline in nature with spherical shape. The zeta potential study revealed that the surface charge of synthesized AgNPs was highly negative (−26.6 mV) and particle size distribution was ranging from ∼35 to 60 nm and the average particle size was about 48 nm determined by dynamic light scattering (DLS). The PGE-AgNPs antidiabetic potential exhibited effective inhibition against α-amylase and α-glucosidase (IC50 ; 65.2 and 53.8 μg/mL, respectively). The PGE-AgNPs showed a dose-dependent response against human liver cancer cells (HepG2) (IC50 ; 70 μg/mL) indicating its greater efficacy in killing cancer cells. They also possessed in vitro free radical-scavenging activity in terms of ABTS (IC50 ; 52.2 μg/mL) and DPPH (IC50 ; 67.1 μg/mL) antioxidant activity. PGE-AgNPs displayed strong antibacterial activity and potent synergy with standard antibiotics against pathogenic bacteria. Thus, synthesized PGE-AgNPs show potential biomedical and industrial applications.